2019
DOI: 10.3390/recycling4030038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Guayule Resin as a Bio-Based Additive on Asphalt–Rubber Binder at Elevated Temperatures

Abstract: This study seeks to find the influence of replacing a portion of the asphalt–rubber binder with the bio-based material “guayule resin.” This replacement could be beneficial in terms of sustainability, economics, and environmental concerns related to the asphalt industry. Nine asphalt–rubber–guayule binders were investigated to find their rheological properties. Consecutively, the study proceeded with five selected binders being compared to the original asphalt (PG64-22). Investigations underwent whole matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The blends were created using a high shear mixer with an accurate heating assembly of a heating mantle and a temperature controller. As a part of the preparation process, the as-received guayule resin (coded G) was stirred at 160℃ for 4 hr with 600 rpm to make sure that no moisture or low molecular weight components were involved (coded G4), as verified in a previous study (Hemida and Abdelrahman, 2019a). The AC was mixed with CRM for 40 min at 190℃ and 3000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The blends were created using a high shear mixer with an accurate heating assembly of a heating mantle and a temperature controller. As a part of the preparation process, the as-received guayule resin (coded G) was stirred at 160℃ for 4 hr with 600 rpm to make sure that no moisture or low molecular weight components were involved (coded G4), as verified in a previous study (Hemida and Abdelrahman, 2019a). The AC was mixed with CRM for 40 min at 190℃ and 3000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…In general, natural resins are amorphous hydrocarbons insoluble in water (7). Concerning the asphalt industry, guayule resin is an asphalt-like material (8). It is flexible adhesive, very susceptible to temperature change and viscoelastic at room temperature, liquid at high temperatures, and solid at low temperatures (8).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the asphalt industry, guayule resin is an asphalt-like material (8). It is flexible adhesive, very susceptible to temperature change and viscoelastic at room temperature, liquid at high temperatures, and solid at low temperatures (8). Hemida and Abdelrahman (8) reported that 25-50% asphalt replacement by guayule resin had the potential to provide better high-temperature performance than the conventional asphalt (PG64) but in case of using crumb rubber modifier (CRM) as an enhancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations